Controlled doping of single crystalline diluted magnetic semiconductor Ga1-xMnxN nanowires - Byeun, Yun-Ki; Han, Kyong-Sop; Choi, Heon-Jin; Choi, Sung-Churl (ELSEVIER SCIENCE SA, 2007)
We report on the optical and magnetic properties of single crystalline dilute magnetic semiconductor Ga1-xMnxN nanowires. The nanowires were fabricated by chemical vapor transport process, and had diameters of < 100 nm and length of several mu m. Controlled doping of manganese in the range of x = 0.01-0.08 was successfully achieved by varying the processing conditions. X-ray diffraction and transmission electron microscopy observation showed that the nanowires are single crystalline without any secondary phases. Photoluminescence emissions of all the doped nanowires were red-shifted (2.8 eV) compare to pure gallium nitride nanowires (3.3 eV) at room temperature. Ferromagnetism up to room temperature was observed in GaN1-xMnxN nanowires with x > 0.04. (c) 2006 Published by Elsevier B.V.
Keywords: MN; FERROMAGNETISM; FILMS